Enzyme replacement therapy with velaglucerase alfa in Gaucher disease: Results from a randomized, double‐blind, multinational, Phase 3 study. Issue 3 (6th February 2013) - Gonzalez, Derlis E.; Turkia, Hadhami Ben; Lukina, Elena A.; Kisinovsky, Isaac; Dridi, Marie‐Françoise Ben; Elstein, Deborah; Zahrieh, David; Crombez, Eric; Bhirangi, Kiran; Barton, Norman W.; Zimran, Ari
<x xml:space="preserve">Abstract</x> Type 1 Gaucher disease (GD1), resulting from glucocerebrosidase deficiency, leads to splenomegaly, hepatomegaly, anemia, thrombocytopenia, and bone involvement. Current standard treatment is enzyme replacement therapy. Velaglucerase alfa is an enzyme replacement product for GD1, with the same amino acid sequence as naturally occurring human glucocerebrosidase. This multinational, Phase 3 trial evaluated the efficacy and safety of two doses of velaglucerase alfa in 25 treatment‐naïve, anemic patients with GD1 (4–62 years of age), randomized to intravenous velaglucerase alfa 60 U/kg (n=12) or 45 U/kg body weight (n=13) every other week for 12 months. The primary endpoint was change from baseline in hemoglobin concentration in the 60 U/kg arm. At 12 months, mean hemoglobin concentrations increased from baseline [60 U/kg: +23.3%; +2.43 g/dL (P<0.001); 45 U/kg: +23.8%; +2.44 g/dL (P<0.001)], as did mean platelet counts [60 U/kg: +65.9%; +50.9 × 109/L (P=0.002); 45 U/kg: +66.4%; +40.9 × 109/L(P=0.01)]. Mean splenic volume decreased from baseline [60 U/kg: −50.4%, from 14.0 to 5.8 multiples of normal (MN) (P=0.003); 45 U/kg: −39.9%, from 14.5 to 9.5 MN (P=0.009)]. No drug‐related serious adverse events or withdrawals were observed. One patient developed antibodies. Velaglucerase alfa was generally well tolerated and effective for adults and children with GD1 in this study. All disease‐specific parameters measured demonstrated clinically meaningful improvements after 12 months. Am. J. Hematol. 88:166–171, 2013. © 2012 Wiley Periodicals, Inc.